Boosting biomass upcycling into 2,5-furandicarboxylic acid via amine-induced protonation on ternary metal-organic heterojunction - Zhao, Haiqing; Shen, Tianxu; Ji, Wei; Lam, Jason Chun-Ho; Hao, Qi; Shen, Laihong; Lin, Richen (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
The electrocatalytic upcycling of biomass-derived 5-hydroxymethylfurfural (HMF) into 2,5-furandicarboxylic acid, a vital building block for bioplastics, represents a transformative approach for advancing bioeconomy. However, efficient electrocatalysis must achieve high product selectivity while simultaneously suppressing side reactions. Here, a ligand-modified electrocatalyst, CoNiCu-HAB (HAB = hexylaminobenzene), was synthesized to boost HMF electrooxidation whilst passivating the competitive oxygen evolution, wherein uncoordinated amine groups induce efficient protonation and electrostatic adsorption of reactive substrates. The CoNiCu layered hydroxides exhibit beneficial synergies: binary CoNi significantly improves reaction kinetics and lowers the onset potential for HMF oxidation (10 mA cm−2 at 1.15 V vs. reversible hydrogen electrode), while Cu effectively inhibits oxygen evolution. Theoretical calculations indicate that the protonation of organic ligands to form -NH3+ species enhances the adsorption of reactive substrates and achieves outstanding Faradaic efficiency exceeding 95 % across a wide potential range. In situ Raman spectroscopy reveals that incorporating organic ligands creates a ternary metal-organic heterojunction structure (MON, where MCo/Ni), the modulation of which increases the availability of active MOOH sites. These results offer a novel strategy for designing high-performance transition metal-based electrocatalysts for biomass upcycling. The work demonstrates an environmentally friendly approach to converting biomass-derived HMF into FDCA, a key bioplastic precursor, using earth-abundant transition metals and minimal energy input, advancing the circular bioeconomy. The work highlights a novel amine-induced protonation strategy that enhances electrostatic adsorption of reactive substrates, significantly improving catalytic performance through formation of -NH3+ species that strengthen substrate binding. [Display omitted] •Ligand-modified catalysts boost FDCA production while passivating oxygen evolution.•Amine protonation forming NH3+ species enhances adsorption of reactive substrates.•Ternary metal-organic heterojunction structure leads to beneficial synergies.•Faradaic efficiency exceeding 95 % across a wide potential range is achieved.